Melt-derived copper-doped ferrimagnetic glass-ceramic for tumor treatment. Issue 22 (15th November 2021) - Miola, Marta; Bruno, Matteo; Gerbaldo, Roberto; Laviano, Francesco; Vernè, Enrica
Abstract: Copper-containing ferrimagnetic glass-ceramic with the following composition: 24.7% SiO2 -8.5% CaO-13.5% Na2 O-3.3% P2 O5 -31% Fe2 O3 -14% FeO–5CuO (wt%) was synthesized by means melt and quenching process both in powder and bulk form. The obtained samples were characterized and compared by means morphological, compositional and structural analyses. The magnetic properties and the ability to release heat were also investigated together with the antimicrobial properties towards S. aureus strain. The obtained results showed that copper introduction and the annealing process influenced the nucleation of crystalline phases; in particular the samples produced in powder form evidenced a low amount of magnetite and thus a reduced hysteresis area and ability to produce heat when exposed to an alternating magnetic field. While Cu-containing samples in the bulk form maintained the magnetic and calorimetric properties of pristine glass-ceramic. Preliminary evaluation of antibacterial properties demonstrated Cu-doped samples were not able to reduce the bacterial proliferation and thus the need to optimize the copper introduction process.